Proyecto de factibilidad para la creación de una academia de música, para la enseñanza - aprendizaje de instrumentos musicales, en la ciudad de Zamora, provincia de Zamora Chinchipe, para el año 2016 - Bermeo Zhañay, Dora Piedad (2017)
The present work titled: Feasibility Project for the creation of a music academy, for the teaching and learning of musical instruments, in the city of Zamora, province of Zamora Chinchipe, for the year 2016, has been developed with the objective To establish the economic and financial feasibility of executing musical services in the sector. In order to give guidance to the research, it was necessary to propose a general objective that is as follows: To carry out a feasibility project for the creation of an academy of music, for the teaching and learning of musical instruments, in the city of Zamora, province Of Zamora Chinchipe, for the year 2016. Likewise, for the fulfillment, specific objectives are drawn which in summary try to develop the following studies: market, technical, administrative, economic-financial, financial evaluation and evaluation of social and environmental impact. In order to meet the stated objectives, different methods and techniques were used; Among the former can be noted the methods: quantitative, deductive, inductive, descriptive and statistical; Among the techniques, the survey was used, which was applied to a representative sample of the population of the Economically Active Population of the Canton Zamora, which was calculated in 392 surveys. In addition, an interview was conducted with one of the companies offering music services. As a result, the following results were obtained: 45% of the respondents like to play musical instruments, 55% consume musical academy services, 54% if they would be willing to use the services of the new company, with these Percentages are determined, the demands, actual and effective power, the latter is multiplied by the per capita consumption that was calculated in 36 hours, and an effective demand is obtained in units of 92,107, which related to the projected supply is obtained a Unsatisfied demand of 67,687 hours in the first year. In the first year of the project with installed capacity is intended to cover 36,88% of unsatisfied demand, 95% of which will be used in year 1, ie 23,712 hours of service will be executed. For the implementation of this project, an investment of USD 20,300.07 is required; Which will be financed, 70% from external sources and 30% from partners. The total cost for the first year is USD 54,327.45; A unit cost of USD 2.28 is established which, with a profit margin of 31%, establishes the P.V.P of USD 2.99 per hour Of the service in the first year, which allows an income of USD 70,898.88. In the financial evaluation, having a positive cash flow in all the project life years, a NPV of USD 30,555.94 is determined; The IRR is 31,22%; The cost-benefit ratio is USD 1.31; The period of capital recovery of 3 years, 8 months and 18 days, the sensitivity is set at 0.99 both in cost increase and decrease in income. The research work is concluded, affirming the feasibility of the project, since all the financial indicators are favorable, ie a NPV of more than 1, the IRR, is higher than the opportunity cost in the R / C for each The invested dollar yields 31 cents of profit, the recovery period of the investment is much lower than the years of useful life of the project and finally it obtains a sensitivity lower than 1, with a cost increase of 21,55% and with A decrease in revenues of 13,59%.